Virtual-Digital Self of Public Human - Vasylieva, L. A. (Anthropological Measurements of Philosophical Research, 2021)
The purpose of the article is distinguishing between "internal" and "external" public human through comprehending the phenomenon of Self in its virtual-digital essence as a popular demonstrative-project space "BETWEEN" aggression and harmony. Theoretical basis of the work is based on the study of the phenomenon of modern human aggression in the virtual-digital space and the "project space" of the living environment through understanding the nature of the human "I". The penetration limits of the Self of the public human into the "project space" are comprehended and the nature of the self-realization and self-search models of human through the "transcendent ego" is revealed. Originality is demonstrated through comprehending the Self phenomenon of the public human, which forms new anthropological research direction and represents a conceptual paradigm of relationship of "human I – publicity – human We – the living space of the Other". Conclusions. The Self of the public human as the space "BETWEEN" does not completely "dissolve" in a separate ontological basis, but is the basis for the formation of his/her "I", while only participation in the existence of others reveals the meaning of his/her own existence. Such interaction requires significant human efforts – skills and competencies of public communication, which are able to create a successful self-identification of a public human without aggression and conflict.